Development of Alternative Plant Tissue Culture Module to Optimize Science Process Skills and Curiosity in Modern Biotechnology Learning in High School (Universitas Negeri Semarang, 2019)
The ideal modern biotechnology is done by practicum. Practicum of plant tissue culture, especially in vitro germination, is intended to train students to perform aseptic activities according to tissue culture characteristics, but not to obtain substantial culture results. This study aims at test the effectiveness of alternative plant tissue culture techniques as a development of alternative plant tissue culture module to optimize science process skills and curiosity learning in high school. The research method uses the ADDIE instructional model. The data taken are in the form of the effectiveness of tissue culture techniques, module validity by media and material experts, module effectiveness seen from the value of science process skills and curiosity, the practicality of the module seen from the response of users namely teachers and students. The results showed that alternative plant tissue culture techniques were effectively used as practical material on the topic of tissue culture in high school to practice science process skills; the modules developed were considered very valid, effective, and practical; the developed modules had characteristics compiled based on simple research on culture network, equipped with images to clarify the practical process, equipped with observation tables as testing data that can guide students to find the concepts taught Based on these results the module is recommended, the use of modules for practicum must manage the time so that everything is in well condition of learning.